2012
DOI: 10.1111/j.1750-3841.2012.02807.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Antioxidant Activity of Leaves, Peels, Stems Bark, and Kernel of Mango (Mangifera indica L.)

Abstract: Bioactive polyphenols, cartenoids, and anthocyanins present in fruits and vegetables are receiving much attention because of their potential antioxidant activity. This study was conducted to determine antioxidant activity of leaves, peels, stem bark, and kernel of mango varieties langra and chonsa. Total phenolic (TPC) and total flavonoid contents (TFCs) in segments of langra ranged from 63.89 to 116.80 mg GAE/g DW and 45.56 to 90.89 mg CE/g DW, respectively, and that of chonsa were 69.24 to 122.60 mg GAE/g DW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 22 publications
6
39
2
1
Order By: Relevance
“…The methanol extract used in the current study results in a similar yield to that of fruits, as reported by our group (20,21), and that of Lantana camara (12.68%), as reported by Ali-Emmanuel et al (22). Together, these results indicate that acidified methanol is a suitable choice for the recovery of phenolic antioxidants.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The methanol extract used in the current study results in a similar yield to that of fruits, as reported by our group (20,21), and that of Lantana camara (12.68%), as reported by Ali-Emmanuel et al (22). Together, these results indicate that acidified methanol is a suitable choice for the recovery of phenolic antioxidants.…”
Section: Resultssupporting
confidence: 89%
“…However, the FRP values of T. portulacastrum reported in this study are comparable with previously published values from certain Brazilian vegetables (29) and fruits (21), but lower than values from medicinal plants investigated by Sultana et al (30). …”
Section: Resultssupporting
confidence: 88%
“…mango (mangifera indica L.) is a popular fruit that can be cultivated in various regions, mainly in the tropics (Sultana et al 2012). Although levels are dependent on cultivars, mango is generally rich Czech J.…”
Section: Sources Of Adfmentioning
confidence: 99%
“…The extraction of active ingredients from Haematococcus pluvialis can be carried out in various ways, such as maceration extraction, solid-phase microextraction and hydrodistillation [9,10]. Usually, these conventional extraction methods are time- and solvent-consuming.…”
Section: Introductionmentioning
confidence: 99%